Performance of laying hens and economic viability of different climatization systems - Silva, Gabriela F. [UNESP] (2013)
Since thermal environment affects production, egg quality and laying hens' mortality rates, it is highly relevant to control the thermal environment within poultry houses so that the best financial profits could be obtained. Three commercial poultry houses with different climatization systems are analyzed in current research: a poultry house with tunnel-like ventilation and pad cooling; a poultry house with natural ventilation and nebulization; a poultry house with simple natural ventilation. Their thermal environment, production, egg quality and laying hens' mortality rates among different poultry houses and at different areas of the same poultry house are compared. Economic profits based on difference in electric energy consumption by climatization systems and on the laying hens' productivity of each poultry house are calculated. Electricity meters were installed within the electrical circuits of the climatization and light systems of the three poultry houses. Data were registered between December 2011 and March 2012 and results showed that all the poultry houses featured heterogeneity in internal thermal environment with faults in the climatization systems. Important differences were reported in egg production and quality caused by overheating. The poultry house with tunnel-like ventilation and pad cooling had the best thermal isolation from the external environment that resulted in a 12.04% improvement in production, decrease between 30 and 40% in laying hens' mortality rates and the best economic result. © G.F. Silva et al., 2013.